Parent’s expectation of sexuality education: implications for teacher education - Mapetla-Nogela, Lineo (University of the Free State, 2014)
Adolescents and young people represent the future of every society. In South Africa however young people are carrying the burden of the HIV pandemic and unintended pregnancies. South Africa is seeing unprecedented levels of sexual violence and increasingly early sexual debuts. The South African Department of Education, in conjunction with the Department of Health and Welfare, developed the National Policy on HIV and AIDS Education which subsequently gave way to a life skills curriculum in schools to address these challenges. With the Minister of Education’s call for parental involvement in the sexuality education of the youth and studies calling for a multi-sectoral approach to try and address these issues, it became imperative to understand the perspectives of parents in this regard. Depending on Wenger’s (1998) Theory of Communities of Practice and Ladson-Billings (1995) Theory of Culturally Relevant Pedagogy, the study explored the expectations of parents of Grade 10 learners of Sexuality Education offered as part of Life Orientation (LO). In this enquiry I sought to answer the following questions: • Whom do parents want to teach sexuality education? • What do parents want from sexuality education? • How do parents want sexuality education to be taught? • What does all this mean for teachers? The study was conducted in the Free State Province and the sample included fourteen participants selected using snowball sampling. Data was collected using In-depth interviews that took place in the homes, places of work of the participants and at restaurants. A focus group was facilitated at one of the participants’ home and five parents participated in this 111 session. Institutional ethical clearance was sought and granted and participants consented to participate in this study. Chapter 1 introduced the research topic and contextualised this study. The chapter outlined the impetus for this study and provided rationale and significance of the study. Chapter 2 introduced literature on sexuality education. In this chapter, the evolution of sexuality education was detailed and the significance of its evolution in response to societal challenges. In Chapter 3 the research methodology is detailed. In this section the methodological orientation of the study was discussed and a rationale for the study was presented. In Chapter 4 findings of the study were presented with the individual in-depth interviews and the focus group being the sources of data. Chapter 5 presents and analyses the data collected and shows how the Communities of Practice and culturally relevant pedagogies frameworks, provided in chapter 2, were applied in the data analysis. This chapter also relates the findings to the literature that was detailed in chapter two. Chapter 6 summarises the study and contains the recommendations, followed by the conclusion of the study.
Dissertation (M.A. (Higher Education Studies))--University of the Free State, 2014
Keywords: Sex instruction for youth; Parent-teacher relationship; Education